Histological Findings of ETosis in Hermansky-Pudlak Syndrome with Pulmonary Fibrosis: A Follow-Up Case Report - Sergio Michael Navarro; Aneel Ashrani; Myung Soo Park; Dong Chen (Journal of Chest Surgery)
Hermansky-Pudlak syndrome (HPS), both alone and in conjunction with pulmonary fibrosis (HPS-PF), is a rare, genetically heterogeneous, autosomal recessive disorder that affects multiple organs, including the lungs. In cases of HPS-PF, pulmonary fibrosis is preceded by local inflammation. We present a case of HPS-PF that exhibited histological evidence of extracellular traps (ETs) ensnaring macrophages, leading to cell death in a process known as ETosis. To our knowledge, ETosis has not been previously reported in the HPS-PF population and may represent a mechanism by which pulmonary fibrosis develops in these patients. Further research is needed to explore the potential connection between ETosis and HPS-PF, as this understanding could offer insights into the disease mechanism and pave the way for the development of novel treatment modalities.